2022
DOI: 10.3390/horticulturae8100953
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Antioxidant, Antimicrobial, Antibiofilm and Anti-Insect Activities of Jasminum grandiflorum Essential Oil

Abstract: The essential oil of Jasminum grandiflorum has very good biological activity. The present study aimed to analyze the chemical composition and biological activity of J. grandiflorum. The main constituents of J. grandiflorum essential oil were benzyl acetate (37%), benzyl benzoate (34.7%) and linalool (9.6%). The antioxidant activity was 58.47%, which corresponds to 220.93 TEAC. The antimicrobial activity was weak to moderate, with inhibition zones ranging from 2.33 to 5.33 mm. The lowest MIC value was against C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…The results of volatile compounds from GC-MS showed that common components such as indole, benzyl acetate and benzyl alcohol could be found in jasmine essential oil, similarly to previous studies [ 9 , 37 ]. In addition to hydrodistillation, a traditional extraction method, linalool, muurolol [ 32 ], and α-farnesene [ 39 ] were the major volatile compounds that were combined to form the jasmine smell.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results of volatile compounds from GC-MS showed that common components such as indole, benzyl acetate and benzyl alcohol could be found in jasmine essential oil, similarly to previous studies [ 9 , 37 ]. In addition to hydrodistillation, a traditional extraction method, linalool, muurolol [ 32 ], and α-farnesene [ 39 ] were the major volatile compounds that were combined to form the jasmine smell.…”
Section: Discussionsupporting
confidence: 87%
“…Common microorganisms such as Staphylococcus aureus (Gram-positive) and Escherichia coli (Gram-negative) were investigated using the MIC method. MIC values from different studies and different extraction methods were reported differently [ 34 , 35 , 36 , 37 ]. However, it can be concluded that jasmine essential oil from HFC-134a extraction also has antimicrobial potential, as indicated by other previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…In the DPPH assay, a DPPH • stock solution (Sigma-Aldrich, Schnelldorf, Germany) was prepared in methanol. The stock solution was then diluted to achieve an absorbance of 0.8 at 515 nm using methanol (Uvasol ® for spectroscopy, Merck, Darmstadt, Germany) [ 25 ]. For the ABTS assay, the ABTS •+ was generated following a previously described procedure [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the third absolute sample from India listed in ▶ Table 4, benzyl acetate (15.5 %), 2,3-epoxy squalene (11.7 %), benzyl benzoate (11.4 %), phytol (10.9 %), isophytol (8.0 %), and phytyl acetate (6.0 %) were obtained as the major compounds [177]. Another study reported the main constituents of the essential oil from J. grandiflorum flowers from Slovakia to be benzyl acetate (37 %), benzyl benzoate (34.7 %) and linalool (9.6 %), (Z)-jasmone (5 %), isophytol (3.3 %), and eugenol (2.1 %) [178], which was quite different from the essential oils in ▶ Table 4. This differences in the chemical compositions are probably due to the different geographical areas or harvest periods of the blossoms [165].…”
Section: Chemical Composition Of Jasmine Essential Oil and Absolutementioning
confidence: 98%
“…Unfortunately, there is also much unserious literature on the jasmine plant, so often, only the extract is reported, without distinguishing between the essential oil or the absolute, which, however, makes a big difference from the ingredients and, thus, properties [168]. In addition, some studies investigated the biological effects of the essential oil [178], while another review claimed that jasmine essential oil had no commercial value [168]. There are only a few studies reporting on the properties of J. grandiflorum absolute extracted from blossoms.…”
Section: Investigations On Biological Activitymentioning
confidence: 99%